2015
DOI: 10.2478/pjs-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

Physician as an Infective Vector at a Department of Surgery

Abstract: 1. Physicians are important factor of bacterial transmission in hospital. 2. Hands, stetoscopes and particularly soles of shoes of medical staff is the source of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Twenty (33.9%) of the studies were performed after sampling HCP hands on general wards, 38,[42][43][44]47,48,51,55,56,61,67,71,73,74,77,78,85,86,89,92 42,44,46,56,60,[62][63][64]71,72,77,82,85 swab was used in 7 (11.9%), 38,47,49,65,73,75,86 and subungual scraping was used in 1 (1.7%). 61 One study did not specify a collection method.…”
Section: Search Results and Study Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty (33.9%) of the studies were performed after sampling HCP hands on general wards, 38,[42][43][44]47,48,51,55,56,61,67,71,73,74,77,78,85,86,89,92 42,44,46,56,60,[62][63][64]71,72,77,82,85 swab was used in 7 (11.9%), 38,47,49,65,73,75,86 and subungual scraping was used in 1 (1.7%). 61 One study did not specify a collection method.…”
Section: Search Results and Study Detailsmentioning
confidence: 99%
“…Across 14 studies, the pooled prevalence of A baumannii was 6.18% (95% CI, 3.05-10.17), 39,43,48,51,52,59,62,65,66,75,78,79,81,83 with a high level of heterogeneity observed (I 2 = 88.7%, P < .001). Regarding geography, 7 studies were conducted in Asia, 43,48,52,66,75,78,81 3 in Europe, 59,65,79 2 in North America, 39,51 and 1 each in South America 62 and Australia. 83 Six studies reported data from the ICU, 39,48,52,59,75,83 5 from the mixed inpatient group, 62,65,66,79,81 4 from the general ward, 43,48,51,78 and 1 from a nursing facility.…”
Section: Gram-negative Organisms (A) P Aeruginosa and A Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…Paduszyńska et al . () studied contamination of shoe soles of physicians before and after patient care rounds using swabs samples processed through the National Coordination center of Poland. Methicillin‐resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis were identified on the shoe soles of 56% of physicians before rounds and 65% after rounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom and the United States, the COVID-19 test results showed that front-line HCWs have a 11-fold increased positive rates as compared to the general community 7 . Secondly, a previous study assessing the risk of infection transmission from physicians to patients through the hands, equipment and enclosing surfaces showed that physicians played an important role in spreading of nosocomial infections 8 . Therefore, the prevention and control of the infection among HCWs have protective effect both on patients and medical staff.…”
Section: Introductionmentioning
confidence: 99%